2022
DOI: 10.18805/ijar.b-5036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-spectrum β-lactamase Producing E. coli and Klebsiella spp. Isolated from Buffaloes in Eastern Plain Zone of Uttar Pradesh

Abstract: Background: Antimicrobial resistance (AMR) due to emergence and spread of Extended-spectrum β-lactamase (ESBL) producing bacteria are point of discussion in both human as well as in animals across the world as it is one of the latest challenges faced by scientific community. The present study highlighted the prevalence of ESBL producing E. coli and Klebsiella spp. isolated from buffaloes in Uttar Pradesh. Methods: Total 240 samples were collected from two district of eastern plain zone of Uttar Pradesh during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Confirmation of these isolates was done by PCR analysis, which revealed total 186 (77.5%) E. coli isolates (Table 2, Fig 1). The findings were in concordance with the findings of Yadav et al (2022a), Kotsoana et al (2019) and Gupta et al (2019). High isolation rate of E. coli in faecal samples may be attributed to high prevalence of E. coli in GIT of ruminants as compared to other members of family Enterobacteriaceae.…”
Section: Resultssupporting
confidence: 88%
“…Confirmation of these isolates was done by PCR analysis, which revealed total 186 (77.5%) E. coli isolates (Table 2, Fig 1). The findings were in concordance with the findings of Yadav et al (2022a), Kotsoana et al (2019) and Gupta et al (2019). High isolation rate of E. coli in faecal samples may be attributed to high prevalence of E. coli in GIT of ruminants as compared to other members of family Enterobacteriaceae.…”
Section: Resultssupporting
confidence: 88%
“…Seventeen isolates (32.08%) were given MIC reading at 0.094, while 13 isolates (24.53%) showed ellipse of inhibition at 0.064. There are few reports in India about the prevalence of ESBL E. coli in mastitis milk from bovines (Bandyopadhyay et al 2015, Paghdar et al 2020, Yadav et al 2023. The results of current study were comparable with other reports of ESBL producers from India.…”
Section: Resultssupporting
confidence: 88%
“…Manoj and Singh (2020) reported maximum sensitivity to chloramphenicol (71.62%) for Gram negative isolates obtained from mastitis cases of Southern Haryana. Yadav et al (2023) reported E. coli isolates showed 100% sensitivity to gentamicin in their study. The lowest resistance to this antibiotic seems to be associated with the restricted usage along with the reduced preference of gentamicin in the treatment of mastitis (Yadav et al 2023).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations